Comercialización y rentabilidad de ferreterías en materiales para la construcción: hierro, cemento, zinc y su relación con la economía del cantón La Maná provincia de Cotopaxi año 2011 - Proaño Yanez, Diana Natali (2014)
Through this research the aim was to know the present situation in which each of the hardware stores are going through, to analyze the relationship with the economy of the La Maná Canton, it determines the main financial indicators of this economic activity having as main objective to analyze the marketing and profitability to suggest improvements in the economy of the business owners, the work began with a description of the definitions of economy , financial indicators and marketing of building materials .